The Story of the War Gamelan Is A Story of Truth - Hendra Santosa; Nina Herlina Lubis; Kunto Sofianto; R.M. Mulyadi (Institut Seni Indonesia Denpasar, 2016)
Stories about gamelan used in warfare are regarded as a character in a fairy tale, a story ofthe past apocryphal. The slogan of history that says no document no historical is an expression that history should not be based solely on “people said